2021
DOI: 10.1021/acssuschemeng.1c04026
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Role of Metal Oxide Catalysts in the CO2 Desorption Process from Nonaqueous Sorbents: An Experimental Study Carried out with 13C NMR

Abstract: The CO2 desorption process from a CO2-saturated nonaqueous sorbent, 2-(2-aminoethoxy)­ethanol (DGA) in diethylene glycol monomethyl ether (DEGMME), was investigated in the absence and presence of four different metal oxides, namely, V2O5, TiO2, WO3, and ZnO, aiming at identifying acid catalysts with the potential to reduce the energy demand for sorbent regeneration. The desorption performances of the DGA-DEGMME solutions with and without catalysts were evaluated in terms of CO2 desorption rate, overall CO2 des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…20 Liang et al 21 reported that the solid catalyst HZSM-5 (Brønsted acid dominated) and γ-Al 2 O 3 (Lewis acid dominated) can reduce the heat duty efficiently in the commercial aqueous monoethanolamine (MEA) solution regeneration process. Recently, Bhatti et al 22 investigated several metal oxide catalysts to improve CO 2 desorption performance in nonaqueous 2-(2-aminoethoxy)ethanolamine (DGA) solution at the desorption temperature of 90 °C; as a result, WO 3 and TiO 2 showed remarkable advantages in enhancing the CO 2 desorption performance. Zhang et al 23 studied SAPO-34 and SO 4 2− /TiO 2 for the catalytic CO 2 desorption from CO 2 -loaded MEA solution under the relatively low temperature of 96 °C; their results revealed that the Brønsted/Lewis acid sites on the catalysts are beneficial to the MEAH + deprotonation and carbamate decomposition, and a high mesopore surface area (MSA) also enhances the catalytic CO 2 desorption performance.…”
Section: ■ Introductionmentioning
confidence: 99%
“…20 Liang et al 21 reported that the solid catalyst HZSM-5 (Brønsted acid dominated) and γ-Al 2 O 3 (Lewis acid dominated) can reduce the heat duty efficiently in the commercial aqueous monoethanolamine (MEA) solution regeneration process. Recently, Bhatti et al 22 investigated several metal oxide catalysts to improve CO 2 desorption performance in nonaqueous 2-(2-aminoethoxy)ethanolamine (DGA) solution at the desorption temperature of 90 °C; as a result, WO 3 and TiO 2 showed remarkable advantages in enhancing the CO 2 desorption performance. Zhang et al 23 studied SAPO-34 and SO 4 2− /TiO 2 for the catalytic CO 2 desorption from CO 2 -loaded MEA solution under the relatively low temperature of 96 °C; their results revealed that the Brønsted/Lewis acid sites on the catalysts are beneficial to the MEAH + deprotonation and carbamate decomposition, and a high mesopore surface area (MSA) also enhances the catalytic CO 2 desorption performance.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Mostly, hindered and tertiary amines were used to enhance the efficiency of desorption of primary amines because such amines exhibit better desorption capabilities. , On the other hand, different classes of desorption catalysts have been applied in past works. It is evident from recent works that Al 2 O 3 among the metal oxides, H-ZSM-5 among zeolites, MCM-41 among mesoporous silica, and SO 4 2– /ZrO 2 among sulfated metal oxides are the most effective candidates for catalyst-aided amine regeneration. , In contrast to zeolite-based catalysts, fewer metal oxides have been used to regenerate amines. This serves as the basis to investigate the performance of several metal oxides. A brief overview of amine regeneration with metal oxides is provided in the Supporting Information (Table S1).…”
Section: Introductionmentioning
confidence: 99%
“…It is evident from recent works that Al 2 O 3 among the metal oxides, H-ZSM-5 among zeolites, MCM-41 among mesoporous silica, and SO 4 2– /ZrO 2 among sulfated metal oxides are the most effective candidates for catalyst-aided amine regeneration. , In contrast to zeolite-based catalysts, fewer metal oxides have been used to regenerate amines. This serves as the basis to investigate the performance of several metal oxides. A brief overview of amine regeneration with metal oxides is provided in the Supporting Information (Table S1). Especially, Bhatti et al reported that metal oxides do not adversely affect the absorption capacity of amines.…”
Section: Introductionmentioning
confidence: 99%
“…According to the best technologies identified so far, postcombustion capture (PCC) has become a commonly accepted method for controlling CO 2 emission from energy-related sources. 3,4 Among the various PCC technologies developed, the chemical absorption using amine-based liquid solutions is considered the most mature and functional method and has several advantages in terms of selectivity for CO 2 , absorption rate, and loading capacity 5 compared to other techniques, such as adsorption with solid sorbents 6 or the use of a membrane contactor. 7 It is well known that there are three kinds of amine that can be used to capture CO 2 from a flue gas, namely, primary, secondary, and tertiary amines.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Unfortunately, the combustion of fossil fuels leads to an inevitable increase in the concentration of carbon dioxide (CO 2 ) in the atmosphere, which is closely related to the so-called global warming, one of the most serious environmental challenges. , As a result, the topic of carbon capture and storage (CCS) has recently attracted a lot of attention from the scientific community and from politicians in every government. According to the best technologies identified so far, postcombustion capture (PCC) has become a commonly accepted method for controlling CO 2 emission from energy-related sources. , Among the various PCC technologies developed, the chemical absorption using amine-based liquid solutions is considered the most mature and functional method and has several advantages in terms of selectivity for CO 2 , absorption rate, and loading capacity compared to other techniques, such as adsorption with solid sorbents or the use of a membrane contactor . It is well known that there are three kinds of amine that can be used to capture CO 2 from a flue gas, namely, primary, secondary, and tertiary amines. , In general, in an aqueous solution, primary and secondary amines can react directly (and rapidly) with CO 2 to form stable carbamates, ensuring efficient separation and a high CO 2 absorption rate but requiring high temperatures (and energy) to regenerate the sorbent.…”
Section: Introductionmentioning
confidence: 99%